2016
DOI: 10.3389/fphar.2016.00423
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Strategies for Renal Cell Carcinoma: From Renal Cancer Cells to Renal Cancer Stem Cells

Abstract: Renal cell carcinoma (RCC) is a common form of urologic tumor that originates from the highly heterogeneous epithelium of renal tubules. Over the last decade, targeting therapies to renal cancer cells have transformed clinical care for RCC. Recently, it was proposed that renal cancer stem cells (CSCs) isolated from renal carcinomas were responsible for driving tumor growth and resistance to conventional chemotherapy and radiotherapy, according to the theory of CSCs; this has provided the rationale for therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 143 publications
(176 reference statements)
0
41
0
Order By: Relevance
“…According to the results of IC 50 evaluation, an RCC cell line demonstrating resistance to sunitinib, termed 786-O/S, was generated by serial treatment of the parental 786-O cell line with various concentrations of sunitinib from 2.5 to 10 µM at 37˚C with the dose given at 1 month intervals. Following continuous culture in the complete medium supplemented with 10 µM sunitinib for >10 passages, identify the IC 50 of 786O/S cells with method mentioned above (concentrations of sunitinib, 5,10,15,20,30,40 and 50 µM). The cells were employed as sunitinib-resistant RCC cells in all subsequent experiments.…”
Section: Determination Of the Half-inhibitory Concentration (Ic 50 ) mentioning
confidence: 99%
“…According to the results of IC 50 evaluation, an RCC cell line demonstrating resistance to sunitinib, termed 786-O/S, was generated by serial treatment of the parental 786-O cell line with various concentrations of sunitinib from 2.5 to 10 µM at 37˚C with the dose given at 1 month intervals. Following continuous culture in the complete medium supplemented with 10 µM sunitinib for >10 passages, identify the IC 50 of 786O/S cells with method mentioned above (concentrations of sunitinib, 5,10,15,20,30,40 and 50 µM). The cells were employed as sunitinib-resistant RCC cells in all subsequent experiments.…”
Section: Determination Of the Half-inhibitory Concentration (Ic 50 ) mentioning
confidence: 99%
“…A wide range of nanodrug delivery systems, including macromolecular NPs, solid lipid NPs, nanoliposomes, polymer micelles, and inorganic nanosomes, could theoretically be used for kidney targeting. [134][135][136] An example is the modified polymyxin-polyetherimide/DNA NPs (115 to 194 nm) synthesized by Oroojalian et al, 33 which were shown to effectively target and transfect megalin-expressing kidney cells and showed low cytotoxicity in vitro and in vivo.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…4,5 Despite the advanced inspection technologies and therapeutic strategies (ie, surgery, radiotherapy, and molecular targeted therapy) are extensively applied, the prognosis of RCC remains poor. 3,6 Although many potential molecular therapeutic biomarkers have been identified in RCC, the accurate mechanism of RCC pathogenesis and progression is still incompletely understood. 7 Therefore, it is urgently needed to uncover the pathogenic mechanism of RCC and develop reliable targets for RCC treatment.…”
Section: Introductionmentioning
confidence: 99%